Korean medicine registry for cognitive disorder: A protocol for prospective observational multi-center study. - Hanbit Jin; Do-Eun Lee; Moon Joo Cheong; Hyungsun Jun; Taena Eom; Seojae Jeon; Dong-Hoon Kang; Hye-Jeong KooK; Daeun Lee; In Chul Jung; Jungtae Leem; Hyung Won Kang (PLoS ONE)
Objective Despite the rapid increase in dementia and cognitive impairment incidence in Korea, research on integrative treatment for cognitive impairment using Korean medicine (KM) is still in its infancy. Thus, prospective studies with systematic data collection are required. This study aims to systematically collect and explore data from patients with dementia and mild cognitive impairment (MCI) who visit KM institutions. The data collected will include the participants' baseline characteristics, cognitive impairment severity, KM diagnosis and treatment status, as well as the factors influencing their choice of integrative medical treatment. Materials and methods This registry study will be conducted from the time of registration in 2024 until December 31, 2029, at Wonkwang University Korean Medicine Hospital, Wonkwang University Jangheung Integrated Medical Hospital, and Daejeon Korean Medicine Hospital of Daejeon University. Approximately 300 participants will be enrolled and visit the hospital annually for data collection. The collected data will include sociodemographic characteristics, laboratory tests, medical device inspections, long-term care information, and various questionnaires related to dementia and cognitive impairment. No predefined interventions or restrictions on treatment will be imposed. Standard and KM treatments for cognitive impairment, including combination therapies, are permitted. As a registry study, the purpose is to investigate the participants' characteristics as outlined in the study objectives, including severity, KM diagnosis and interventions, and clinical outcomes. This epidemiological study is designed to include additional statistical analyses in response to research questions that emerge over time. Discussion This study represents a pioneering effort in the KM field establishing the first registry of its kind focusing on dementia and MCI. This study aims to identify the characteristics of patients with dementia and MCI who visit KM institutions, explore the factors influencing KM treatment, and observe clinical outcomes according to KM pattern identification, providing evidence based on real-world data.